2016
DOI: 10.18596/jotcsa.49500
|View full text |Cite
|
Sign up to set email alerts
|

DETERMINATION of the TRACE ELEMENT LEVELS in HAIR of SMOKERS and NON-SMOKERS by ICP-MS

Abstract: For at least 50 years, determination of the trace element levels in human hair has been used to assess environmental and vocational exposure to toxic elements. As compared to other biological matrices (e.g. blood, urine), human hair is stable and therefore useful as a matrix. In this study, analyses of toxic and essential trace elements, such as Cd, Pb, Cu, and Fe were done in hair samples which we collected from male smokers (10 people) and non-smokers (10 people) who live in Diyarbakır, Turkey and concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…; , during their studies, found that the concentration of metals Cr, Cu, Ni, Co, Cd, Zn, and As in the hair increases with age. The concentration of these metals in the hairs of smokers was higher than that of non-smokers He et al, 2016); Oral (2016) found that the concentration of Pb in the hairs of smokers was 2.5 times that of non-smokers. The accumulation of these metals in the hairs of cigarette smokers was higher than that of pipe smokers (Alrobaian & Arida, 2019).…”
Section: Hairsmentioning
confidence: 97%
“…; , during their studies, found that the concentration of metals Cr, Cu, Ni, Co, Cd, Zn, and As in the hair increases with age. The concentration of these metals in the hairs of smokers was higher than that of non-smokers He et al, 2016); Oral (2016) found that the concentration of Pb in the hairs of smokers was 2.5 times that of non-smokers. The accumulation of these metals in the hairs of cigarette smokers was higher than that of pipe smokers (Alrobaian & Arida, 2019).…”
Section: Hairsmentioning
confidence: 97%